STUDI KASUS PERAN PENYULUH AGAMA ISLAM DALAM REHABILITASI SOSIAL PADA DEWASA TERLANTAR DI UNIT REHABILITASI SOSIAL BINA KARYA MADIUN - farah nadiyah (ROSYADA: Islamic Guidance and Counseling, 2021)
Abstract This study aims to find the efforts of Islamic counseling supervisors in solving the problems of neglected adults at the Social Rehabilitation Unit of Bina Karya Madiun in Ponorogo. This research uses a qualitative descriptive case study research approach. Data collection techniques used are through observation, interviews, and documentation. For technical data analysis using data reduction, data presentation, and drawing conclusions. The results of the study briefly show that the efforts made by Islamic counseling supervisors in solving neglected adult problems according to the field are planning, implementation and evaluation. Islamic counseling guidance methods in meeting the needs of neglected adults according to the field are lectures, dialogues and questions and answers, consultations, talaqqi. Keywords: role of Islamic religious instructor, neglected adults, guidance method metode